COMPOSIÇÃO QUÍMICA DA ÁGUA DE CHUVA EM RIO CLARO (SP) - Dos Santos, Vinícius [UNESP]; Gastmans, Didier [UNESP] (Instituto Geologico, 2016)
The rainwater chemistry in Rio Claro (SP) was evaluated based on composite weekly samples collected at the Centro de Estudos Ambientais (CEA), UNESP Rio Claro. Data set evaluation includes statistical analysis of cation and anion concentrations, carried out via a Pearson correlation matrix, principal component analysis (PCA), and estimation of the weighted mean of the volume of precipitation. The HYSPLIT model of tracking atmospheric particles was used to identify the main trajectories of air masses for the rain that fell in the Rio Claro area and the possible interaction of the surface area with the atmosphere. The rain is characteristically slightly acid (pH 4.75 to 6.81) with low electrical conductivity (from 4.12 to 29.3 μS cm-1). Rainwater incorporates elements and compounds from two main sources. HCO3 - originates from atmospheric CO2 produced by plant respiration and present in industrial and vehicle emissions. Ca2+, Mg2+, Mn2+ and K+ are directly related to the geology of the region, and specifically to emissions due to mining activities for the ceramic industry around Rio Claro, while NH4 +, NO3 - and Pb2+ can be associated with industrial and vehicle emissions. Despite the multiple origins for the elements within the rainwater, natural sources account for about 40% of the compounds.
Chemical composition of rainwater in Rio Claro, SP
Keywords: Atmospheric pollution; Ceramic industries; Rainwater composition; Rio Claro